1997
DOI: 10.2105/ajph.87.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Stable behaviors associated with adults' 10-year change in body mass index and likelihood of gain at the waist.

Abstract: OBJECTIVES: The purpose of this study was to identify behaviors associated with change in body mass index or with weight gain at the waist. METHODS: A cohort of 79236 White, non-Hispanic, healthy adults was questioned in 1982 and 1992 about diet and 10 physical activities. Estimates were made of the mean effects of stable behaviors on 10-year change in body mass index and on odds ratios for gain at the waist. RESULTS: Ten-year changes in body mass index was associated positively with meat consumption and smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
120
2
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 45 publications
13
120
2
7
Order By: Relevance
“…However, the present study failed to establish a significant relationship at the 95 % confidence level. Thus the present results conflict with multiple studies reporting that higher meat intake is associated with obesity (27,(32)(33)(34)(35)(36)(37) . Low intakes of meats and processed meats have been associated with lower increases in BMI over time; however, further research is needed to identify foods in the meat group that are specifically related to the increased risk of both obesity and abdominal obesity among women (13) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the present study failed to establish a significant relationship at the 95 % confidence level. Thus the present results conflict with multiple studies reporting that higher meat intake is associated with obesity (27,(32)(33)(34)(35)(36)(37) . Low intakes of meats and processed meats have been associated with lower increases in BMI over time; however, further research is needed to identify foods in the meat group that are specifically related to the increased risk of both obesity and abdominal obesity among women (13) .…”
Section: Discussioncontrasting
confidence: 99%
“…Meat intake has been associated with obesity (27,(32)(33)(34)(35)(36)(37) . However, the present study failed to establish a significant relationship at the 95 % confidence level.…”
Section: Discussionmentioning
confidence: 99%
“…In the CARDIA study of US young adults, beer was also positively associated with WHR in both genders (Slattery et al, 1992). By contrast, in a subsample of the US Cancer Prevention Study II, there was no clear association between beer intake and 10 y changes in 'weight gain at the waist' in men or women, and beer intake was negatively associated with 10 y changes in BMI in both genders (Kahn et al, 1997). In a French study, beer (and wine) intake was positively associated with WHR in women but not in men, and inversely with BMI in women (Dallongeville et al, 1998).…”
Section: Discussionmentioning
confidence: 88%
“…The literature on the relation of beer-to-obesity indices is sparse and inconsistent (Slattery et al, 1992;Duncan et al, 1995;Kahn et al, 1997;Dallongeville et al, 1998;Rosmond & Bjorntorp, 1999). Since obesity, particularly abdominal, is a strong risk factor for cardiovascular disease (Larsson, 1992), and beer is becoming increasingly popular, we thought that this question deserves some attention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that women reduce the amount and intensity of physical activity as they age at about twice the rate of aging men, 33 but compared to men women can achieve weight loss and weight maintenance with exercise that is lower in intensity and duration. 28,31,34 Empirical research also shows that women tend to gain more weight than men over time. 2,5,9 Our models suggest that this is due primarily to the lower T1 female weight and possibly to a lower female activity habit.…”
Section: Discussionmentioning
confidence: 99%